Correct Me if I'm Wrong: Groups Outperform Individuals in the Climate Stabilization Task - Xie, Belinda; Hurlstone, Mark J.; Walker, Iain (Frontiers in Psychology, 2018)
Avoiding dangerous climate change requires ambitious emissions reduction. Scientists agree on this, but policy-makers and citizens do not. This discrepancy can be partly attributed to faulty mental models, which cause individuals to misunderstand the carbon dioxide (CO2) system. For example, in the Climate Stabilization Task (hereafter, ‘CST’) (Sterman & Booth-Sweeney, 2007), individuals systematically underestimate the emissions reduction required to stabilize atmospheric CO2 levels, which may lead them to endorse ineffective ‘wait-and-see’ climate policies. Thus far, interventions to correct faulty mental models in the CST have failed to produce robust improvements in decision-making. Here, in the first study to test a group-based intervention, we found that success rates on the CST markedly increased after participants deliberated with peers in a group discussion. The group discussion served to invalidate the faulty reasoning strategies used by some individual group members, thus increasing the proportion of group members who possessed the correct mental model of the CO2 system. Our findings suggest that policy-making and public education would benefit from group-based practices.